Molecular Modeling of β-Cyclodextrin Inclusion Complexes with some N-2-chloroethyl, N-Nitroso, N’-sulfamoyl Molecules - FATIHA, MADI; SOUMEYA, SERIDI; DJAMELEDDINE, KHATMI (Asian Journal of Chemistry, 2010)
The use of molecular modeling techniques to study inclusion complexes attract a great importance. Because the combination of the experimental results and those obtained by calculation became a very powerful means to understand the inclusion complexation phenomena. In present study the computer simulations was carried out by using the Hyperchem 6.0 software to study the inclusion of N-nitroso, N-(2-chloroethyl), N´-sulfamoylpiperidine, product with antitumor activity, in the β-cyclodextrin. The inclusion of CENS to cyclodextrin cavity was carried out according to two orientations and three orientations. We found that using MM+ force field, the difference of studied orientation is, kcal/mol. This difference exceeds 25 kcal/mol when these systems were put in box water. The energy complexation was determined kcal/mol. The heat of formation and binding energy were calculated with AM1 and PM3 semi empirical methods.